Come, pretty babe, a consort song by William Byrd dealing with a sensitive issue (Ex Chordis, 2023)
In England, during the last decades of the Sixteenth Century (in the middle of the Elizabethan Age), a popular type of music was the consort songs. These were music pieces for voice and consort of violas that William Byrd (c. 1540-1623) was particularly skilled at creating. One of Byrd’s unpublished songs was Come, pretty babe, which was quite controversial for its time because it dealt with the topic of illegitimate motherhood. The song is a lullaby where the mother shares with her little boy the pain and anguish of their difficult situation. This paper translates the literary text of the song into Italian and discusses its social context. Moreover, the paper provides a brief overview of Byrd’s consort songs and hypothesizes the reasons why Come, pretty babe was not published by the Britannicae Musicae Parens.
Keywords: William Byrd; Consort Song; Consort of Viols; Elizabethan Age; Illegitimacy